HTLV 1/2 Prevalence and risk factors in individuals with HIV/AIDS in Pernambuco, Brazil - Mirela Lopes Ribeiro; Juliana Prado Gonçales; Viviane Martha Santos de Morais; Libia Cristina Rocha Vilela Moura; Maria Rosângela Cunha Duarte Coêlho (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: Apart from masking the diagnosis of AIDS in patients with HIV/AIDS, human T-cell lymphotropic virus (HTLV), when present, also increases the risk of myelopathies and neurological disease in these patients. METHODS: Disease prevalence was estimated by ELISA and confirmed by Western blot. RESULTS: The coinfection rate was 1.5% (11/720); 10 of 11 patients had HTLV-1, and the remaining one had HTLV-2. The majority were male, over 40 years old, and of pardo color (ethnicity). CONCLUSIONS: There was no association between the risk factors examined and HTLV/HIV coinfection. This is the first study to report the occurrence of HTLV-2 in Pernambuco.